A Multi-Institutional Retrospective Analysis of Oncologic Outcomes for Patients With Locally Advanced Cervical Cancer Undergoing Platinum-Based Adjuvant Chemotherapy After Concurrent Chemoradiotherapy. (12th February 2021) - Wu, Ning; Su, Xing; Song, Honglin; Li, Ying; Gu, Fei; Sun, Xiaoge; Li, Xiaofan; Cheng, Guanghui
Objective: To evaluated the oncologic outcomes associated with platinum-based adjuvant chemotherapy following concurrent chemoradiotherapy (CCRT) in the management of patients with locally advanced cervical cancer (LACC). Methods: A total of 695 patients with FIGO stage IB2, IIA2, IIB-IVA LACC treated at 6 medical facilities were enrolled and divided into 2 groups: 478 were assigned to CCRT alone (CCRT group) and 217 to adjuvant chemotherapy after CCRT (CCRT-ACT group). The treatment outcomes were retrospectively compared and reported after the propensity score matching (PSM) analysis. Results: With a median follow-up of 56.4 months, no statistically significant differences were found in overall survival (OS), disease-free survival (DFS), progression-free survival (PFS) and distance metastasis-free survival (DMFS) between 2 groups. In CCRT-ACT group, patients with lymph nodes involvement or squamous cell carcinoma (SCC) had significantly longer DMFS, but no significant benefit in survival outcomes were observed with more than 2 cycles of adjuvant chemotherapy. Moreover, patients with a high level of CA125 (>20.5U/mL) or SCC-Ag (>22.8μg/L) had a relatively better DFS or PFS, and grade 3-4 acute hematological toxicity, late urinary and lower gastrointestinal complications and diarrhea symptom were more frequent in CCRT-ACT group. Conclusions: Adjuvant chemotherapy after CCRT has a potential role in further improving disease control for LACC patients with lymph nodal-metastasis or SCC with a high level of CA125 or SCC-Ag. Due to increased treatment-related complications and diarrhea symptom affecting the quality of life, post-CCRT adjuvant chemotherapy with excessive cycles was not be considered as the most appropriate choice in general.